A Roadmap for Policy-Relevant Sea-Level Rise Research in the United Arab Emirates - Melville-Rea, Hannah; Eayrs, Clare; Anwahi, Nasser; Burt, John A.; Holland, Denise; Samara, Fatin; Paparella, Francesco; Al Murshidi, Ahmed Hassan; Al-Shehhi, Maryam Rashed; Holland, David M. (Frontiers in Marine Science, 2021)
The United Arab Emirates (UAE) has a long-term policy horizon, financial capital, and vision for a sustainable knowledge-based economy. These characteristics uniquely situate it as a potential leader for sea-level rise research. Climate science is already growing, and at the center of the UAE's pivot towards climate research is a growing concern for sea-level rise. Over 85% of the UAE's population and more than 90% of the nation’s infrastructure is within a few meters of present-day sea-level. With its low-lying and shallow-sloping geography (about 35cm per km), this high-value coastline, including the rapidly expanding cities of Dubai and Abu Dhabi, is particularly vulnerable to sea-level rise. Meanwhile, limited regional research and data scarcity creates deep uncertainty for sea-level projections. In the wake of COVID-19, the UAE is doubling down on government-led coordination for community health and security. We set out a potential roadmap for the UAE to capitalize on its strengths to create usable and relevant sea-level projections for the region. With a newly established Climate Change Research Network, the UAE government is beginning to draw together universities and research centers for "furthering effective data collection and management, and advancing policy-relevant research on climate impacts and adaptation". By consolidating ideas from scientists within the UAE, we identify promoters and barriers to data gathering, information sharing, science-policy communication, and funding access. Our paper proposes pathways forward for the UAE to integrate sea-level science with coastal development and form best practices that can be scaled across climate science and throughout the region.